Innovation in Aqidah Akhlak Learning: Implementing Think Pair Share to Cultivate Religious Moderation Values - Azar, Dhea; Pahrudin, Agus; Hasanah, Ida Faridatul; Irawan, Rudy; Fitriani, Fitriani; Susanti, Agus (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The rapid pace of globalization and digital technology, coupled with the inherent social diversity in Indonesia, increases the risk of social conflict and intolerance. In this context, conventional teaching methods in religious education often fail to deeply instill the values of religious moderation needed to navigate such a complex environment. This study will investigate and describe the development of the Think Pair Share (TPS) instructional model as a strategic tool for cultivating religious moderation values among students within the subject of Faith and Moral Education (Akidah Akhlak). A descriptive qualitative approach was employed at State Islamic High School (MAN) 1 Bandar Lampung. Data were gathered through in-depth interviews with teachers of Faith and Moral studies and students, followed by thematic analysis to understand the implementation and impact of the learning model. The findings indicate that the implementation of the TPS model yields significant positive outcomes. The